Dendrochronological reconstruction of long-term precipitation patterns in Basaseachi National Park, Chihuahua, Mexico - Irby, Christen M.; Fulé, Peter Z.; Yocom, Larissa L.; Díaz, José Villanueva (Instituto de Ecología, A.C., 2013)
The purpose of this study was to reconstruct the precipitation at Basaseachi National Park (BNP) inChihuahua, Mexico.Tree-ring samples from pine species including Pinus durangensis, P. lumholtzii andP.engelmannii were collected in and near BNP and they were cross-dated with existing chronologies.Ring widths of each sample were measured and models to remove non-climatic trends from the data wereapplied. The relationship between precipitation from the weather station in Yécora, Sonora, and the ringwidth indices were modeled using a bivariate linear regression (r2 = 0,59, p<0.01). It was found that precipitationfrom the months of October, December, February and April was most highly correlated with treering growth. The reconstruction extends 225 years from 2007-1782. During this time period there werethirteen severe droughts, ten of which affected large areas in northern and central Mexico.